Identification and expression analysis of c-type and g-type lysozymes genes after Aeromonas hydrophila infection in African catfish - Nasrullah, Hasan; Nababan, Yanti Inneke; Yanti, Dwi Hany; Hardiantho, Dian; Nuryati, Sri; Junior, Muhammad Zairin; Ekasari, Julie; Alimuddin, Alimuddin (Jurnal Akuakultur Indonesia, 2019)
ABSTRACTLysozymes play an important role in the first line of defense in fish and potentially used as an immunity status biomarker and immune responses evaluation in fish, which often found in two types, i.e. chicken-type and goose-type (c- and g-type, respectively). To recent, the information related to the sequences and the expression analysis of the c- and g-type lysozyme genes in African catfish is still limited. In the present study, we report a partial cloning and mRNA expression analysis of c-type and g-type lysozymes in African catfish Clarias gariepinus. We have successfully cloned and partially identify the c-type, and g-type lysozyme genes of C. gariepinus, which consist of 594 and 560 of coding sequences, respectively. Catalytic and other conserved residues were identified by multiple sequences alignment and they showed high similarity with other teleost fish species. mRNA levels of the genes were analyzed by using qPCR method and their expressions in the spleen, liver, and head kidney were rapidly modulated after Aeromonas hydrophila injection, with different patterns were observed in each organ. These results confirmed that c- and g-type lysozymes played an important role in non-specific immunity against A. hydrophila infection. This study provided valuable information that can be used to understand the African catfish immune systems for better disease and stress management in C. gariepinus culture.Keywords: lysozymes, gene identification, gene expression, bacterial infection, African catfish ABSTRAKLisozim berperan dalam sistem pertahanan dini pada ikan dan sangat potensial digunakan sebagai marka status imunitas dalam evaluasi respons imun. Lisozim umum ditemukan dalam dua tipe pada ikan: tipe-ayam (tipe-c) dan tipe-angsa (tipe-g). Informasi terkait sekuens gen dan ekspresi gen kedua tipe lisozim pada ikan lele dumbo sangat terbatas. Pada penelitian ini, kami melaporkan kloning gen secara parsial, dan analisis ekspresi gen dari kedua tipe lisozim pada ikan lele dumbo C. gariepinus. Sekuens parsial gen lisozim tipe-c dan tipe-g yang berhasil diidentifikasi adalah sepanjang 594 dan 560 pasang basa. Situs katalitik dan residu khas memiliki tingkat kesamaan yang tinggi dengan spesies ikan yang lain. Analisis mRNA dilakukan dengan metode quantitative PCR (qPCR). Ekspresi kedua gen di jaringan ginjal depan, limpa, dan hati dengan cepat terinduksi pasca infeksi bakteri A. hydrophila dengan pola yang berbeda. Hasil ini menunjukkan bahwa lisozim tipe-c dan tipe-g memiliki peran yang sangat penting dalam sistem imun ikan lele dumbo terhadap infeksi A. hydrophila. Penelitian ini menghasilkan informasi penting yang dapat digunakan untuk mempelajari sistem imun ikan lele dumbo dan sebagai acuan dalam penanganan dan manajemen penyakit pada budidaya ikan lele dumbo.Kata kunci: lisozim, identifikasi gen, ekspresi gen, infeksi bakteri, ikan lele dumbo